Analisis Pengaruh Firm Size, Risiko Keuangan, dan Profitabilitas Terhadap Risiko Bisnis pada Perusahaan Sektor Makanan dan Minuman di Bursa Efek Indonesia - Andi Meriam (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
Companies in the food and beverage consumption goods sector are mostly affected by a number of factors that affect risk. Variables that are quite dominant influence on business risk include firm size, financial risk and profitability. This study uses a quantitative approach to analyze the effect of firm size, financial risk and profitability on business risk in the food consumption goods sector on the IDX. The results showed that the three variables together influenced the business risk of the consumer goods sector while partially the profitability variable was the most influential on business risk in the food and beverage sector companies on the IDX.